Design Simulation and Radiation Optimization of 90Sr Isotope Generator Radioactive Source - YANG Liqun, JIA Nannan, ZHOU Jian, LI Yefan, TANG Jun (Journal of Isotopes, 2024)
90Sr has strong bremsstrahlung radiation, before manufacturing the radioisotope heat source, it is necessary to first simulate the composition of the 90SrTiO3 ceramic pellet, design the structure of the fuel cladding, and evaluate the bremsstrahlung radiation of the pellet and fuel cladding according to the manufacturing process. In order to reduce the exposure dose of thermoelectric conversion devices, the article based on β shielding principle has proposed three methods to reduce bremsstrahlung radiation from radioactive sources. The MCNP simulation results show that using aluminum foil to wrap the core blocks, optimizing the core block ingredients, and adding boron nitride gaskets can effectively reduce bremsstrahlung. All three methods will change the design size of the fuel cladding, and the engineering feasibility of wrapping aluminum foil is poor. The research results will guide the design and manufacturing of the source part of the Sr-90 thermoelectric generator, and provide theoretical methods for radiation optimization of the generator.